THE EFFECT OF SMILE THERAPY AND EDUCATION IN PREGNANCY ON DECREASING LEVELS OF ANXIETY IN PRIM GRAVID - Sriyatin S (Journal of Maternity Care and Reproductive Health, 2019)
Anxiety in pregnant women is due to pregnancy physical changes, preparing labor, and caring for children after childbirth. One intervention to overcome anxiety is smile therapy. Smiling is one of the easiest ways to reduce stress and make friendships. Smiling is not only an important nonverbal indicator of happiness but also as a medicine to deal with life's stress. This study aimed to determine the effect of smile therapy on reducing anxiety levels in Prim gravid women aged 4-8 months in the PHC in Cirebon City. This research was a quantitative study using a quasi-experimental design with a nonrandomized Pretest-Posttest Control Group Design. The number of samples in the study was 44 pregnant women. Data were analyzed by paired sample test with a significance level of 5% (0.05). The results showed a value of p = 0.009, there was a difference in anxiety level scores between the intervention group and the control group after smile therapy intervention. The intervention of effective therapy to reduce the anxiety of prim gravid women during pregnancy, there is a needs further application of this therapy to other maternal phases such as labor or post-partumKeywords: Anxiety, pregnancy education, prim gravid, smile therapy